Complex dynamics and chaos control of electricity markets with heterogeneous expectations. (29th June 2013) - Yang, Hongming; Yang, Songping; Zhao, Junhua; Dong, Zhaoyang
SUMMARY A novel model of electricity market dynamics is proposed in this paper. The model consists of the difference equations embedded within the problem of optimization of market clearing. Decision‐making processes of different market participants under bounded rationality and adaptive expectations are considered in the proposed model. Moreover, the model can accurately reflect the process of market clearing and take into account the complex network constraints. Different market status, such as stable Nash equilibrium, periodic oscillation and chaos, are quantitatively analyzed. For unfavorable chaotic fluctuations in economic performance, use of the parameter perturbation control method in electricity market is proposed. The measures required for driving the market from the chaotic state to stable Nash equilibrium are suggested to provide an important theoretical basis for effectively regulating the electricity market. Copyright © 2013 John Wiley & Sons, Ltd.